Maternal iron kinetics and maternal–fetal iron transfer in normal-weight and overweight pregnancy. Issue 4 (15th December 2021) - Stoffel, Nicole U; Zimmermann, Michael B; Cepeda-Lopez, Ana C; Cervantes-Gracia, Karla; Llanas-Cornejo, Daniel; Zeder, Christophe; Tuntipopipat, Siriporn; Moungmaithong, Sakita; Densupsoontorn, Narumon; Quack Loetscher, Katharina; Gowachirapant, Sueppong; Herter-Aeberli, Isabelle
ABSTRACT: Background: Inflammation during pregnancy may aggravate iron deficiency (ID) by increasing serum hepcidin and reducing iron absorption. This could restrict iron transfer to the fetus, increasing risk of infant ID and its adverse effects. Objectives: We aimed to assess whether iron bioavailability and/or iron transfer to the fetus is impaired in overweight/obese (OW) pregnant women with adiposity-related inflammation, compared with normal-weight (NW) pregnant women. Methods: In this prospective study, we followed NW ( n  = 43) and OW ( n  = 40) pregnant women who were receiving iron supplements from the 14 th week of gestation to term and followed their infants to age 6 mo. We administered 57 Fe and 58 Fe in test meals mid-second and mid-third trimester, and measured tracer kinetics throughout pregnancy and infancy. Results: In total, 38 NW and 36 OW women completed the study to pregnancy week 36, whereas 30 NW and 27 OW mother–infant pairs completed the study to 6 mo postpartum. Both groups had comparable iron status, hemoglobin, and serum hepcidin throughout pregnancy. Compared with the NW, the OW pregnant women had 1 ) 43% lower fractional iron absorption (FIA) in the third trimester ( P = 0.033) with median [IQR] FIA of 23.9% [11.4%–35.7%] and 13.5% [10.8%–19.5%], respectively; and 2 ) 17% lower maternal–fetal iron transfer from the first tracer ( P = 0.051) with median [IQR] maternal–fetal iron transfer of 4.8% [4.2%–5.4%] and 4.0% [3.6%–4.6%], respectively. Compared with the infants born to NW women, infants born to OW women had lower body iron stores (BIS) with median [IQR] 7.7 [6.3–8.8] and 6.6 [4.6–9.2] mg/kg body weight at age 6 mo, respectively ( P = 0.024). Prepregnancy BMI was a negative predictor of maternal–fetal iron transfer (β = −0.339, SE = 0.144, P = 0.025) and infant BIS (β = −0.237, SE = 0.026, P = 0.001). Conclusions: Compared with NW, OW pregnant women failed to upregulate iron absorption in late pregnancy, transferred less iron to their fetus, and their infants had lower BIS. These impairments were associated with inflammation independently of serum hepcidin. This trial was registered at clinicaltrials.gov as NCT02747316.